The Image of Russia and Russians as Seen by Polish University Students - Awramiuk-Godun, Alina; Wites, Tomasz (Quaestiones Geographicae, 2013)
The results presented in this study are part of a joint research project undertaken in 2011 by the University of Warsaw and the University of St. Petersburg entitled “The perception of Polish-Russian relations by students in Poland and Russia”. The main purpose of the research conducted in Poland was to investigate the beliefs and attitudes of students at the University of Warsaw toward Russia and Russians. Students are open to the surrounding reality, conscious of the mental and spatial proximity that links Poles and Russians, and aware of the problems that define the present-day Polish-Russian relations. A vast majority of participants are people who possess a fairly extensive knowledge of various aspects of life in Russia and express sympathy for Russia and Russian people. In the opinion of the authors, the results of the above study can be useful to teachers at universities, especially those that deal with European, socio-cultural and geographical subjects.